Water-based negative oxygen ion additive, preparation method and application thereof, silk with negative oxygen ion release function and preparation method thereof
By performing specific treatment of natural mineral complexes and combining them with silk, the problem that ordinary silk does not have the function of negative oxygen ion release is solved, and silk preparation with high negative oxygen ion release is achieved, improving air quality and human health level.
Patent Information
- Application Number
- CN202510377448.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-06-27
AI Technical Summary
Ordinary silk does not have the function of releasing negative oxygen ions and cannot enjoy the health benefits brought by negative oxygen ions.
By grinding a specific natural mineral composite, acid leaching-alkali boiling combined treatment, drying and airflow grinding, and surface modification with silane coupling agent and/or titanate coupling agent, an aqueous negative oxygen ion additive with a high negative oxygen ion release amount is prepared, and then combined with silk to impart the silk to negative oxygen ion release function.
The prepared silk with negative oxygen ion release function can significantly increase the amount of negative oxygen ion release, improve air quality, improve human health, and have excellent formaldehyde and TVOC removal functions, suitable for use in the fields of home and health care.
Smart Images

Figure CN120211101A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aqueous negative oxygen ion auxiliary agent and a preparation method and application thereof, a silk with a negative oxygen ion releasing function and a preparation method thereof, and belongs to the technical field of daily necessities. Background Art
[0002] In today's era, people's yearning for a healthy life is becoming stronger and stronger. This trend has led to a sharp increase in the market demand for functional textiles. Among them, negative oxygen ions have gradually become the focus of public attention because of their many positive effects on human health. From the perspective of improving air quality, negative oxygen ions are like "scavengers" of the air. They can absorb tiny particles such as dust, smoke and bacteria suspended in the air, effectively purify the air, and make people feel as if they are in the depths of the forest, breathing fresh and natural air. In terms of promoting metabolism, negative oxygen ions can accelerate the material exchange of human cells, enhance cell vitality, and make the organs of the body function better. Poor sleep quality is a problem that plagues many people, and negative oxygen ions can regulate the nervous system, relieve mental stress, help people enter a deep sleep state faster, and improve sleep quality.
[0003] Silk, as a natural fiber, has long been loved by consumers for its excellent skin-friendliness and unparalleled comfort. However, ordinary silk has an obvious shortcoming, that is, it does not have the function of releasing negative oxygen ions. This means that when using ordinary silk products, people cannot enjoy a series of health benefits brought by negative oxygen ions.
[0004] In view of this, it is particularly necessary to develop a silk with high negative oxygen ion release function. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a method for preparing an aqueous negative oxygen ion additive. The present invention first grinds a specific natural mineral composite, then performs an acid leaching-alkali boiling combined treatment, then performs a drying treatment and air flow grinding at a high temperature, and finally uses a silane coupling agent and / or a titanate coupling agent to perform surface modification. The method provided by the present invention can obtain an aqueous negative oxygen ion additive with high negative oxygen ion release and excellent dispersion stability. The preparation method provided by the present invention is simple and convenient for industrial production.
[0006] The second object of the present invention is to provide an aqueous negative oxygen ion auxiliary agent, which has a very high negative oxygen ion release amount and high stability.
[0007] The third object of the present invention is to provide a method for preparing silk with the function of releasing negative oxygen ions. The silk prepared by this method has a high negative oxygen ion release amount.
[0008] To achieve the above object, the first aspect of the present invention is to provide a preparation method of an aqueous negative oxygen ion additive, and the method includes:
[0009] (1) In the presence of a solvent, grinding a natural mineral complex to obtain Intermediate I;
[0010] (2) Soaking the Intermediate I with an acid solution to obtain Intermediate II;
[0011] (3) Boiling the Intermediate II with an alkali solution to obtain Intermediate III;
[0012] (4) Sequentially drying and air-grinding the Intermediate III to obtain Intermediate IV;
[0013] (5) Mixing the Intermediate IV with a silane coupling agent and / or a titanate coupling agent for reaction to obtain the aqueous negative oxygen ion additive;
[0014] Wherein, the natural mineral complex contains 40 - 60 wt% of rock salt ore and 40 - 60 wt% of six-ring stone;
[0015] Alternatively, the natural mineral complex contains 35 - 45 wt% of tourmaline, 25 - 35 wt% of opal, 15 - 25 wt% of rock salt ore and 5 - 15 wt% of six-ring stone.
[0016] The innovation of the present invention lies in using a natural mineral complex of rock salt ore and six-ring stone in a specific ratio or a natural mineral complex of tourmaline, opal, rock salt ore and six-ring stone in a specific ratio as a raw material to prepare an aqueous negative oxygen ion additive. Through the mutual cooperation among the natural minerals, the deficiencies of a single excitation method can be overcome, the negative oxygen ion release amount of the functional powder composite system can be increased, and more application scenarios can be adapted. For example, the excitation of six-ring stone depends on the content of gaseous water in the air (air humidity), and in an aqueous medium, ferric ions are reduced to ferrous ions to release negative oxygen ions; rock salt ore depends on the environmental temperature, and its internal trace elements will release negative oxygen ions at a higher temperature; tourmaline releases negative oxygen ions through a photocatalytic mechanism combined with a pyroelectric effect and a piezoelectric effect. Through the mutual cooperation among the substances in the natural mineral complex system provided in the present invention, the negative oxygen ion release amount can be further enhanced.
[0017] The present invention first sequentially grinds a specific natural mineral complex, performs combined acid leaching-alkali boiling treatment, drying and air-grinding, and finally performs surface modification on it with a silane coupling agent and / or a titanate coupling agent, and can obtain an aqueous negative oxygen ion additive with a relatively large negative oxygen ion release amount. The present invention can grind the powder to a particle size D through liquid-phase grinding. 90≤300 nm, increasing the release amount of negative oxygen ions. Acid soaking can remove impurities in the composite system. If acid soaking is not carried out, it will lead to excessive impurity content, affecting the release amount of negative oxygen ions; alkali boiling can hydroxylate the surface of mineral powder and stimulate the reaction activity. If alkali boiling is not carried out, it will lead to a decrease in surface activity, and ineffective graft modification cannot occur during the reaction with the surface modifier, resulting in aggregation and precipitation during application; air-flow grinding can disperse the aqueous negative oxygen ion additive to avoid agglomeration. Surface modification with silane coupling agent and / or titanate coupling agent can improve the dispersibility and stability of the powder composite system.
[0018] As a preferred solution, in step (1), the mass ratio of the natural mineral complex to the solvent is 1:3 - 8.
[0019] As a preferred solution, the solvent is water or an ethanol aqueous solution.
[0020] As a preferred solution, the concentration of ethanol in the ethanol aqueous solution is 2 - 20 wt%.
[0021] As a preferred solution, the acid solution is a hydrochloric acid solution, and the concentration of the acid solution is 0.01 - 0.1 mol / L.
[0022] As a preferred solution, the alkali solution is a sodium hydroxide solution and / or a potassium hydroxide solution, and the concentration of the alkali solution is 0.01 - 0.1 mol / L.
[0023] As a preferred solution, control the conditions of the grinding treatment so that the particle size D of the solid material in Intermediate I 90 ≤300 nm. Further preferably 20 - 300 nm. The inventor found that in this preferred case, an aqueous negative oxygen ion additive with a higher release amount of negative oxygen ions can be obtained. If the particle size is too large, the release amount becomes smaller, and if the particle size is too small, it will lead to uncontrollable agglomeration during subsequent processing and use, resulting in a smaller release amount.
[0024] As a preferred solution, control the conditions of the air-flow grinding so that the particle size D of Intermediate IV 90 ≤250 nm.
[0025] As a preferred solution, the time of the soaking treatment is 10 - 30 min.
[0026] As a preferred solution, the alkali boiling is carried out under boiling conditions, and the time of the alkali boiling is 10 - 60 min. The inventor found that during low-temperature alkali treatment, the powder cannot be fully activated, resulting in insufficient subsequent surface modification, while at high temperatures, the activation efficiency of the powder is higher, and thus surface modification is easier.
[0027] It should be noted that the present invention has no special requirements for the amounts of the acid solution for the soaking treatment and the alkali solution for the alkali cooking, and those known in the art can be used. Exemplarily, it is only necessary to completely immerse the solid material.
[0028] As a preferred embodiment, the conditions for the drying treatment include: a temperature of 150 to 400 °C and a time of 4 to 10 h. The inventors have found that under these conditions, the lattice energy of the mineral can be increased, thereby improving the electron mobility, increasing the efficiency of electrons being captured by water or oxygen in the air, and thus increasing the negative oxygen ion release amount.
[0029] As a preferred embodiment, the total mass ratio of the intermediate IV to the silane coupling agent and / or titanate coupling agent is 100:2 to 8.
[0030] As a preferred embodiment, the conditions for the reaction in step (5) include: a temperature of 120 to 150 °C and a time of 1 to 3 h.
[0031] As a preferred embodiment, the reaction in step (5) is carried out by a high-speed kneading machine under the condition of vacuum stirring.
[0032] The second aspect of the present invention provides an aqueous negative oxygen ion auxiliary agent prepared by the preparation method of the aqueous negative oxygen ion auxiliary agent described in the first aspect above.
[0033] The third aspect of the present invention provides the application of the aqueous negative oxygen ion auxiliary agent described in the second aspect above in the preparation of silk with negative oxygen ion release function.
[0034] The fourth aspect of the present invention provides a preparation method of silk with negative oxygen ion release function, and the method includes:
[0035] S1: Mix the aqueous negative oxygen ion auxiliary agent with water and stir for 20 to 30 min under the condition of a rotation speed ≥ 2000 r / min, and adjust the pH value of the solution to 6 to 6.5 to obtain an auxiliary agent solution;
[0036] S2: Immerse the silk in the auxiliary agent solution for 1 to 10 h to obtain silk I;
[0037] S3: Dehydrate the silk I and then successively carry out drying and balancing treatments to obtain silk with negative oxygen ion release function;
[0038] The aqueous negative oxygen ion auxiliary agent is the aqueous negative oxygen ion auxiliary agent described in the second aspect above.
[0039] It should be noted that in step S3, there are no special requirements for the dehydration conditions, and those known in the art can be adopted. As a more preferred solution, the dehydration conditions include: a rotation speed of 1000 - 1500 r / min and a time of 8 - 20 min.
[0040] As a preferred solution, in step S3, the solution removed after dehydration is recycled. The specific method includes: after filtering the solution, adding a water-based negative oxygen ion additive with a mass concentration of 5% - 8% and then reusing it, and the number of recycling times ≤ 3 times.
[0041] As a preferred solution, the reagent for adjusting the pH value is citric acid or sodium bicarbonate.
[0042] As a preferred solution, the concentration of the water-based negative oxygen ion additive in water is 5 - 15 wt%.
[0043] As a preferred solution, the mass ratio of the silk to the additive solution is 1:10 - 40.
[0044] As a preferred solution, the silk is top cocoon and / or douppioni silk.
[0045] As a preferred solution, the length of the silk ≥ 50 cm and the moisture content ≤ 8 wt%.
[0046] As a preferred solution, in step S2, the method further includes: ultrasonically cleaning the silk with water and then centrifugally dehydrating it in sequence, and then immersing the silk that has been centrifugally dehydrated into the additive solution.
[0047] As a preferred solution, the conditions for ultrasonic cleaning include: an ultrasonic frequency of 30 - 50 kHz and a cleaning time of 8 - 12 min. Cleaning can remove the grease and residual impurities on the surface of the silk.
[0048] As a preferred solution, the conditions for centrifugal dehydration include: a rotation speed of 700 - 900 r / min and a time of 4 - 10 min.
[0049] It should be noted that in order to improve the penetration efficiency of the negative oxygen ion additive, during the process of soaking the silk in the additive solution, the silk can be turned over every 1 - 3 h or the solution can be circulated using a circulation pump to soak the silk in a dynamic solution.
[0050] As a preferred solution, the drying conditions include: successively pre-drying, main-drying and final-drying the silk I, and the pre-drying conditions include: temperature of 35 - 45°C, humidity of 25 - 35%RH, and time of 50 - 70min; the main-drying conditions include: temperature of 50 - 58°C, humidity of 12 - 20%RH, and time of 2.5 - 3.5h; the final-drying conditions include: temperature of 59 - 65°C, humidity ≤ 10%RH, and time of 0.5 - 1.5h.
[0051] As a preferred solution, the conditions for the equilibration treatment include: temperature of 25 ± 2°C, humidity of 45 ± 5%RH, and standing for 24 - 48h until moisture absorption equilibrium is reached.
[0052] It should be noted that moisture absorption equilibrium means that the water content of the silk with negative oxygen ion release function is 8 - 10wt%.
[0053] The fifth aspect of the present invention provides silk with negative oxygen ion release function prepared by the preparation method of silk with negative oxygen ion release function described in the fourth aspect above.
[0054] Compared with the prior art, the present invention has at least the following advantages:
[0055] (1) The aqueous negative oxygen ion additive prepared by the method of the present invention can be excited under different conditions after compounding, with a large negative oxygen ion release amount and high stability, and can be used to prepare silk with negative oxygen ion release function.
[0056] (2) The silk with negative oxygen ion release function provided by the present invention has a significant negative oxygen ion release function, can improve air quality, and enhance the human health level.
[0057] (3) The negative oxygen ion additive solution of the present invention can be recycled and reused, which is environmentally friendly and economical.
[0058] (4) The silk quilt prepared from the silk with negative oxygen ion release function has excellent functions of removing formaldehyde and TVOC, and is suitable for use in the fields of home and health care. Description of the Drawings
[0059] Figure 1 SEM diagram of the aqueous negative oxygen ion additive prepared in Preparation Example 1. Detailed Embodiments
[0060] The endpoints and any values disclosed in this text for ranges are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the values between the endpoints of each range, between the endpoints of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this text.
[0061] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative efforts still fall within the protection scope of the present invention.
[0062] Unless otherwise specifically stated, various raw materials, reagents, instruments, and equipment used in the present invention can be obtained through market purchases or can be prepared by existing methods.
[0063] Silk pretreatment: Select superior cocoon silk (silk length ≥ 50 cm, moisture content ≤ 8%), remove impurities and broken fibers, and then use deionized water for ultrasonic cleaning (frequency 40 kHz, time 10 min) to remove surface grease and residual impurities. Subsequently, perform centrifugal dehydration (rotation speed 800 r / min, time 5 min).
[0064] The preparation examples of the present invention are used to prepare the aqueous negative oxygen ion additive. The dosage of the natural mineral complex in the following preparation examples is 20 Kg.
[0065] Preparation Example 1
[0066] Composition of the natural mineral complex: rock salt ore (50 wt%), hexagonal stone (50 wt%);
[0067] (1) Mix the natural mineral complex with an ethanol aqueous solution (ethanol concentration is 10 wt%), and grind it with an ultra-fine ball mill until the particle size D 90 of the natural mineral complex is 120 nm to obtain Intermediate I;
[0068] The mass ratio of the dosage of the natural mineral complex to the ethanol aqueous solution is 1:4;
[0069] (2) Soak Intermediate I in a 0.06 mol / L hydrochloric acid solution for 25 min, and wash the acid-soaked Intermediate I twice with clear water to obtain Intermediate II;
[0070] (3) Under the condition that the solution is boiling, use a 0.06 mol / L sodium hydroxide solution to perform alkali boiling on the above Intermediate II for 40 min to obtain Intermediate III;
[0071] (4) Dry the above intermediate III at 300 °C for 6 h, and then crush it under a pressure of 9 Kg to a particle size D 90 ≤180 nm to obtain intermediate IV;
[0072] (5) React the above intermediate IV and titanate coupling agent (NDZ-201) in a high-speed kneader under vacuum and stirring conditions (temperature is 140 °C, time is 1.5 h) to obtain an aqueous negative oxygen ion additive.
[0073] The mass ratio of the amount of intermediate IV to the titanate coupling agent is 100:2.5.
[0074] The present invention exemplarily provides an SEM image of the aqueous negative oxygen ion additive prepared in this preparation example, specifically see Figure 1 From Figure 1 it can be seen that there are a small amount of uneven structures in the powder, but it is mainly in the form of flakes, indicating that a new powder system has actually been formed after a series of treatments on the compounding system, rather than a simple physical blending.
[0075] Preparation Example 2
[0076] Composition of natural mineral complex: tourmaline (40 wt%), opal (30 wt%), rock salt ore (20 wt%), hexacyclic stone (10 wt%);
[0077] (1) Mix the natural mineral complex with an aqueous ethanol solution (ethanol concentration is 8 wt%), and grind it with an ultra-fine ball mill to a particle size D of the natural mineral complex 90 of 200 nm to obtain intermediate I;
[0078] The mass ratio of the amount of the natural mineral complex to the aqueous ethanol solution is 1:6;
[0079] (2) Soak intermediate I in a 0.08 mol / L hydrochloric acid solution for 28 min, and wash the acid-soaked intermediate I with water 3 times to obtain intermediate II;
[0080] (3) Under the condition that the solution is boiling, boil intermediate II with a 0.08 mol / L sodium hydroxide solution for 45 min to obtain intermediate III;
[0081] (4) Dry the above intermediate III at 380 °C for 6 h, and then crush it under a pressure of 10 Kg to a particle size D 90 ≤250 nm to obtain intermediate IV;
[0082] (5) React the above intermediate IV, titanate coupling agent (NDZ-311), and silane coupling agent (KH-560) in a high-speed kneader under vacuum and stirring conditions (temperature is 120 °C, time is 3 h) to obtain an aqueous negative oxygen ion additive.
[0083] The mass ratio of the amounts of intermediate IV, titanate coupling agent, and silane coupling agent is 100:4:2.
[0084] Comparative Preparation Example 1
[0085] Composition of natural mineral complex: tourmaline (60 wt%), opal (40 wt%);
[0086] (1) Mix the natural mineral complex with an aqueous ethanol solution (ethanol concentration is 10 wt%) and grind it with an ultra-fine ball mill until the particle size D of the natural mineral complex 90 is 150 nm to obtain intermediate I;
[0087] The mass ratio of the amounts of the natural mineral complex and the aqueous ethanol solution is 1:5;
[0088] (2) Soak intermediate I in a 0.05 mol / L hydrochloric acid solution for 20 min, and wash the acid-soaked intermediate I with clear water 3 times to obtain intermediate II;
[0089] (3) Under the condition that the solution is boiling, boil intermediate II with a 0.05 mol / L sodium hydroxide solution for 35 min to obtain intermediate III;
[0090] (4) Dry the above intermediate III at 280 °C for 7 h, and then crush it under a pressure of 8.5 Kg until the particle size D 90 ≤ 200 nm to obtain intermediate IV;
[0091] (5) React the above intermediate IV and silane coupling agent (KH-550) in a high-speed kneader under vacuum and stirring conditions (temperature is 140 °C, time is 1.5 h) to obtain an aqueous negative oxygen ion additive.
[0092] The mass ratio of the amounts of intermediate IV and silane coupling agent is 100:3.
[0093] Comparative Preparation Example 2
[0094] Composition of natural mineral complex: tourmaline (70 wt%), rock salt ore (30 wt%);
[0095] (1) Mix the natural mineral complex with an aqueous ethanol solution (ethanol concentration is 10 wt%) and grind it with an ultra-fine ball mill until the particle size D of the natural mineral complex 90It is 250 nm to obtain Intermediate I;
[0096] The mass ratio of the natural mineral complex to the aqueous ethanol solution is 1:5;
[0097] (2) Soak Intermediate I in a 0.04 mol / L hydrochloric acid solution for 15 min, and wash the acid-soaked Intermediate I with water 3 times to obtain Intermediate II;
[0098] (3) Under the condition that the solution is boiling, boil Intermediate II with a 0.04 mol / L sodium hydroxide solution for 25 min to obtain Intermediate III;
[0099] (4) Dry the above Intermediate III at 250 °C for 8 h, and then crush it under a pressure of 8 Kg to a particle size D 90 ≤100 nm to obtain Intermediate IV;
[0100] (5) React the above Intermediate IV, silane coupling agent (KH-570) and titanate coupling agent (NDZ-311) in a high-speed kneader under vacuum and stirring conditions (temperature is 140 °C, time is 1.5 h) to obtain an aqueous negative oxygen ion additive.
[0101] The mass ratio of Intermediate IV, silane coupling agent and titanate coupling agent is 100:2:2.
[0102] Comparative Preparation Example 3
[0103] Composition of the natural mineral complex: opal (55 wt%), hexagonal stone (45 wt%);
[0104] (1) Mix the natural mineral complex with an aqueous ethanol solution (ethanol concentration is 10 wt%), and grind it with an ultrafine ball mill to a particle size D of the natural mineral complex 90 It is 250 nm to obtain Intermediate I;
[0105] The mass ratio of the natural mineral complex to the aqueous ethanol solution is 1:5;
[0106] (2) Soak Intermediate I in a 0.03 mol / L hydrochloric acid solution for 18 min, and wash the acid-soaked Intermediate I with water 2 times to obtain Intermediate II;
[0107] (3) Under the condition that the solution is boiling, boil Intermediate II with a 0.03 mol / L sodium hydroxide solution for 50 min to obtain Intermediate III;
[0108] (4) Dry the above Intermediate III at 350 °C for 5 h, and then crush it under a pressure of 7.5 Kg to a particle size D 90≤120 nm, to obtain Intermediate IV;
[0109] (5) React the above Intermediate IV with a silane coupling agent (KH-792) using a high-speed kneader under vacuum and stirring conditions (temperature: 140 °C, time: 1.5 h) to obtain an aqueous negative oxygen ion additive.
[0110] The mass ratio of the amount of Intermediate IV to the silane coupling agent is 100:3.
[0111] Comparative Preparation Example 4
[0112] This comparative preparation example was carried out by referring to a method similar to that of Preparation Example 1. The difference is that in this comparative example, six-ring stone was not added, that is, the addition amount of rock salt ore was 100 wt%.
[0113] Comparative Preparation Example 5
[0114] Steps (1) and (2) are the same as those in Preparation Example 1;
[0115] Step (3): Dry the above Intermediate II at 300 °C for 6 h, and then crush it under a pressure of 7 Kg to a particle size D 90 ≤180 nm, to obtain Intermediate III;
[0116] (4) React the above Intermediate III with a titanate coupling agent (NDZ-201) using a high-speed kneader under vacuum and stirring conditions (temperature: 140 °C, time: 1.5 h) to obtain an aqueous negative oxygen ion additive.
[0117] The mass ratio of the amount of Intermediate III to the titanate coupling agent is 100:2.5.
[0118] Comparative Preparation Example 6
[0119] This comparative preparation example was carried out by referring to a method similar to that of Preparation Example 1. The difference is that in this comparative example, rock salt ore was not added, that is, the addition amount of six-ring stone was 100 wt%.
[0120] Examples 1 to 4 of the present invention are used to prepare silk with negative oxygen ion release function, and the aqueous negative oxygen ion additives used in the following examples are all the aqueous negative oxygen ion additives prepared in Example 1.
[0121] Example 1
[0122] (1) Mix an aqueous negative oxygen ion additive (5 kg) with deionized water (95 kg), and stir for 30 min using a high-speed shear emulsifier at a rotation speed of 2000 r / min, and adjust the pH value of the solution to 6.16 to obtain an additive solution; Test the solution stability: no precipitation and no stratification after standing for 24 hours, viscosity 0.6;
[0123] (2) Immerse the pretreated silk in the above-mentioned auxiliary agent solution for 8 h to obtain Silk 1-I; the mass ratio of the auxiliary agent solution to the pretreated silk is 20:1, and manually turn it over every 2 hours;
[0124] (3) Dehydrate and centrifuge the above-mentioned Silk 1-I in a three-foot centrifuge (rotation speed 1200 r / min, time 10 min) to remove the excess solution, and the solution recovery rate is 85% (85 Kg);
[0125] (4) Then pre-dry the dehydrated silk at a temperature of 40 °C and a humidity of 30% RH for 60 min, then main-dry it at a temperature of 55 °C and a humidity of 15% RH for 3 h, and continue to final-dry it at a temperature of 60 °C and a humidity ≤ 10% RH for 1 h to obtain silk with negative oxygen ion release function.
[0126] Example 2
[0127] (1) Mix the aqueous negative oxygen ion auxiliary agent (7.5 kg) and deionized water (92.5 kg), stir with a high-speed shear emulsifier at a rotation speed of 2500 r / min for 30 min, and adjust the pH value of the solution to 6.16 to obtain the auxiliary agent solution; Test the solution stability: no precipitation and no stratification after standing for 24 hours, viscosity 0.7;
[0128] (2) Immerse the pretreated silk in the above-mentioned auxiliary agent solution for 10 h to obtain Silk 2-I; the mass ratio of the auxiliary agent solution to the pretreated silk is 20:1, and manually turn it over every 2 hours;
[0129] (3) Dehydrate and centrifuge the above-mentioned Silk 2-I in a three-foot centrifuge (rotation speed 1200 r / min, time 10 min) to remove the excess solution, and the solution recovery rate is 88% (88 Kg);
[0130] (4) Then pre-dry the dehydrated silk at a temperature of 40 °C and a humidity of 30% RH for 60 min, then main-dry it at a temperature of 55 °C and a humidity of 15% RH for 3 h, and continue to final-dry it at a temperature of 60 °C and a humidity ≤ 10% RH for 1 h to obtain silk with negative oxygen ion release function.
[0131] Example 3
[0132] (1) Mix the aqueous negative oxygen ion auxiliary agent (10 kg) and deionized water (90 kg), stir with a high-speed shear emulsifier at a rotation speed of 3000 r / min for 30 min, and adjust the pH value of the solution to 6.16 to obtain the auxiliary agent solution; Test the solution stability: no precipitation and no stratification after standing for 24 hours, viscosity 0.8;
[0133] (2) Immerse the pretreated silk in the above-mentioned auxiliary agent solution for 1 h to obtain silk 3-I; the mass ratio of the auxiliary agent solution to the pretreated silk is 20:1, and the flow rate of the solution circulation pump is 0.5 m3 / h;
[0134] (3) Dehydrate and centrifuge the above-mentioned silk 3-I in a three-foot centrifuge (rotation speed 1200 r / min, time 10 min) to remove the excess solution, and the solution recovery rate is 90% (90 Kg);
[0135] (4) Then dehydrate the silk successively at a temperature of 40 °C and a humidity of 30% RH for 60 min, then subject it to main drying at a temperature of 55 °C and a humidity of 15% RH for 3 h, and continue to subject it to final drying at a temperature of 60 °C and a humidity ≤ 10% RH for 1 h to obtain silk with negative oxygen ion release function.
[0136] Example 4
[0137] (1) Mix the water-based negative oxygen ion auxiliary agent (12 kg) and deionized water (88 kg), stir with a high-speed shear emulsifier at a rotation speed of 3500 r / min for 30 min, and adjust the pH value of the solution to 6.16 to obtain the auxiliary agent solution; test the solution stability: no precipitation and no stratification after standing for 24 hours, viscosity 0.85;
[0138] (2) Immerse the pretreated silk in the above-mentioned auxiliary agent solution for 2 h to obtain silk 4-I; the mass ratio of the auxiliary agent solution to the pretreated silk is 20:1, and the flow rate of the solution circulation pump is 0.5 m3 / h.
[0139] (3) Dehydrate and centrifuge the above-mentioned silk 4-I in a three-foot centrifuge (rotation speed 1200 r / min, time 10 min) to remove the excess solution, and the solution recovery rate is 92% (92 Kg);
[0140] (4) Then dehydrate the silk successively at a temperature of 40 °C and a humidity of 30% RH for 60 min, then subject it to main drying at a temperature of 55 °C and a humidity of 15% RH for 3 h, and continue to subject it to final drying at a temperature of 60 °C and a humidity ≤ 10% RH for 1 h to obtain silk with negative oxygen ion release function.
[0141] Examples 5 to 8 of the present invention are experiments on the recycling effect of the solution obtained by dehydration and centrifugation.
[0142] Example 5:
[0143] (1) Make up the solution volume: Take all the filtrate obtained in Example 1 and mix it with the auxiliary agent solution prepared in Example 1 to prepare 100 Kg of auxiliary agent solution I;
[0144] (2) Prepare silk with negative oxygen ion release function by referring to the method of Example 1 using the auxiliary agent solution I obtained in step (1).
[0145] Test the negative oxygen ion release amount of the prepared silk with negative oxygen ion release function, and the result is 1850 ions / cm³.
[0146] Example 6:
[0147] (1) Make up the solution volume: Take all the filtrate obtained in Example 2 and mix it with the auxiliary agent solution prepared in Example 2 to prepare 100 Kg of auxiliary agent solution I;
[0148] (2) Prepare silk with negative oxygen ion release function by referring to the method of Example 2 using the auxiliary agent solution I obtained in step (1);
[0149] (3) Use the solution obtained in step (2) to continue making up the solution volume according to the method of step (1), and then prepare silk with negative oxygen ion release function according to the method of step (2).
[0150] Test the average negative oxygen ion release amount of the prepared silk with negative oxygen ion release function, and the result is 2950 ions / cm³.
[0151] Example 7: Conduct an experiment on the recycling of the filtrate obtained in Example 3
[0152] (1) Make up the solution volume: Take all the filtrate obtained in Example 3 and mix it with the auxiliary agent solution prepared in Example 3 to prepare 100 Kg of auxiliary agent solution I;
[0153] (2) Prepare silk with negative oxygen ion release function by referring to the method of Example 3 using the auxiliary agent solution I obtained in step (1);
[0154] (3) Use the solution obtained in step (2) to continue making up the solution volume according to the method of step (1), and then prepare silk with negative oxygen ion release function according to the method of step (2), and repeat this step once.
[0155] Test the average negative oxygen ion release amount of the prepared silk with negative oxygen ion release function, and the result is 3150 ions / cm³.
[0156] Example 8
[0157] (1) Make up the solution volume: Take all the filtrate obtained in Example 4 and mix it with the auxiliary agent solution prepared in Example 4 to prepare 100 Kg of auxiliary agent solution I;
[0158] (2) Prepare silk with negative oxygen ion release function by referring to the method of Example 4 using the auxiliary agent solution I obtained in step (1);
[0159] (3) Use the solution obtained in step (2) to continue to make up the solution volume according to the method in step (1), and then use the method in step (2) to prepare silk with negative oxygen ion release function, and repeat this step once.
[0160] The average negative oxygen ion release amount of the prepared silk with negative oxygen ion release function was tested to be 3300 ions / cm³.
[0161] Test example
[0162] Test the negative oxygen ion release amount, dispersion stability and formaldehyde degradation rate of the aqueous negative oxygen ion additive prepared in the above preparation example. The specific results are shown in Table 1.
[0163] The test method for negative oxygen ion release amount is: GB / T 30128-2014 static method.
[0164] The test method for dispersion stability is: dynamic light scattering method. The dynamic light scattering method is a commonly used method for characterizing the dispersion state of nanoparticles. This method obtains the size distribution and dispersion state of nanoparticles by measuring the Brownian motion of nanoparticles in solution.
[0165] The test method for formaldehyde degradation rate is: JC / T 1074-2008.
[0166] Table 1
[0167]
[0168]
[0169] Test the negative oxygen ion release performance of the silk with negative oxygen ion release function prepared in the above example. The test results are shown in Table 2.
[0170] Test device:
[0171] Use a sealed glass chamber (size 50×30×20 cm), with a negative oxygen ion detector (model: COM-3200Pro) inside, and test after zeroing the environmental background value.
[0172] Test process:
[0173] (1) Evenly spread 100 g of silk sample in the chamber, seal it and then start the detector;
[0174] (2) Continuously monitor for 20 minutes, record the fluctuation range of negative oxygen ion concentration, and take the average of the maximum value and the minimum value as the release amount;
[0175] Standard test conditions: temperature 25±2°C, humidity 45%, release amount ≥2000 ions / cm³.
[0176] The test methods for formaldehyde removal rate and TVOC removal rate are: JC / T 1074-2008.
[0177] Table 2
[0178] Negative oxygen ion release amount (ions / cm3) Formaldehyde removal rate (%) TVOC removal rate (%) Example 1 1900 86.2 61.9 Example 2 3080 91.4 72.6 Example 3 3210 91.8 73.4 Example 4 3350 93.5 74.2
[0179] Application Example: Preparation of Silk Quilt
[0180] Filler Structure:
[0181] (1) Layer the silk with negative oxygen ion releasing function prepared in Example 2 (each layer is 2-3 cm thick), with a total filling amount of 1.5-2.5 kg / bed, and use the cross-laying process to avoid caking.
[0182] (2) Wrap the outer layer of the filler with antibacterial non-woven fabric (gram weight 20 g / m2) to prevent fiber migration.
[0183] Outer Fabric:
[0184] (1) Select a blended fabric (70% cotton + 30% negative oxygen ion functionalized polyester), with a warp density ≥ 200 threads per inch and a weft density ≥ 180 threads per inch, and a sewing stitch density of 3 mm / stitch.
[0185] (3) Final Product Test:
[0186] Formaldehyde / TVOC Removal Rate: Refer to the GB / T 18801-2015 standard to test the removal rate in a 24-hour closed environment (formaldehyde ≥ 80%, TVOC ≥ 60%);
[0187] Negative Oxygen Ion Release Amount: The retention rate of the negative oxygen ion release amount of the quilt product (compared with the same mass of negative oxygen ion releasing silk) ≥ 80%.
[0188] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the technical concept scope of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.
Claims
1. A method for preparing an aqueous negative oxygen ion additive, characterized in that: The method includes: (1) grinding the natural mineral complex in the presence of a solvent to obtain an intermediate I; (2) soaking the intermediate I in an acid solution to obtain an intermediate II; (3) using an alkaline solution to alkali-boil the intermediate II to obtain an intermediate III; (4) subjecting the intermediate III to drying treatment and airflow grinding in sequence to obtain intermediate IV; (5) mixing the intermediate IV with a silane coupling agent and / or a titanate coupling agent to react to obtain the aqueous negative oxygen ion auxiliary agent; The natural mineral composite contains 40-60 wt% of rock salt and 40-60 wt% of hexacyclic stone; Alternatively, the natural mineral composite contains 35-45wt% of tourmaline, 25-35wt% of opal, 15-25wt% of rock salt and 5-15wt% of hexachlorobenzene.
2. The method for preparing an aqueous negative oxygen ion additive according to claim 1, characterized in that: In step (1), the mass ratio of the natural mineral complex to the solvent is 1:3-8.
3. A method for preparing an aqueous negative oxygen ion additive according to claim 1 or 2, characterized in that: The acid solution is a hydrochloric acid solution, and the concentration of the acid solution is 0.01-0.1 mol / L; And / or, the alkaline solution is a sodium hydroxide solution and / or a potassium hydroxide solution, and the concentration of the alkaline solution is 0.01-0.1 mol / L.
4. A method for preparing an aqueous negative oxygen ion additive according to claim 1 or 2, characterized in that: The grinding conditions are controlled so that the particle size D of the solid material in the intermediate I is 90 ≤300nm; And / or, the conditions of the airflow milling are controlled so that the particle size D of the intermediate IV is 90 ≤250nm.
5. A method for preparing an aqueous negative oxygen ion additive according to claim 1 or 2, characterized in that: The soaking time is 10 to 30 minutes; And / or, the alkali boiling is carried out under boiling conditions, and the alkali boiling time is 10 to 60 minutes; And / or, the drying treatment conditions include: a temperature of 150 to 400° C. and a time of 4 to 10 hours.
6. An aqueous negative oxygen ion auxiliary agent prepared by the preparation method of an aqueous negative oxygen ion auxiliary agent according to any one of claims 1 to 5.
7. Use of the aqueous negative oxygen ion auxiliary agent according to claim 6 in preparing silk with negative oxygen ion releasing function.
8. A method for preparing silk with negative oxygen ion releasing function, characterized in that: The method includes: S1: Mix the aqueous negative oxygen ion additive with water, stir for 20 to 30 minutes at a speed of ≥2000 r / min, and adjust the pH value of the solution to 6 to 6.5 to obtain an additive solution; S2: soaking the silk in the auxiliary agent solution for 1 to 10 hours to obtain silk I; S3: dehydrating the silk I and then performing drying and balancing treatments in sequence to obtain silk with a negative oxygen ion releasing function; The aqueous negative oxygen ion auxiliary agent is the aqueous negative oxygen ion auxiliary agent according to claim 6.
9. The method for preparing silk with negative oxygen ion releasing function according to claim 8, characterized in that: The concentration of the aqueous negative oxygen ion additive in water is 5 to 15 wt %; And / or, the mass ratio of the silk to the auxiliary agent solution is 1:10-40; And / or, the drying conditions include: pre-drying, main drying and final drying of the silk I in sequence, and the pre-drying conditions include: temperature of 35-45°C, humidity of 25-35%RH, and time of 50-70min; the main drying conditions include: temperature of 50-58°C, humidity of 12-20%RH, and time of 2.5-3.5h; the final drying conditions include: temperature of 59-65°C, humidity ≤10%RH, and time of 0.5-1.5h.
10. Silk with negative oxygen ion releasing function prepared by the method for preparing silk with negative oxygen ion releasing function as claimed in claim 8 or 9.